Hepatocyte-Conditional Knockout of Phosphatidylethanolamine Binding Protein 4 Aggravated LPS/D-GalN-Induced Acute Liver Injury via the TLR4/NF-κB Pathway - Qu, Xiao-qin; Chen, Qiong-feng; Shi, Qiao-qing; Luo, Qian-qian; Zheng, Shuang-yan; Li, Yan-hong; Bai, Liang-yu; Gan, Shuai; Zhou, Xiao-yan (Frontiers in Immunology, 2022)
Acute liver injury (ALI) is a disease that seriously threatens human health and life, and a dysregulated inflammation response is one of the main mechanisms of ALI induced by various factors. Phosphatidylethanolamine binding protein 4(PEBP4) is a secreted protein with multiple biological functions. At present, studies on PEBP4 exist mainly in the field of tumors and rarely in inflammation. This study aimed to explore the potential roles and mechanisms of PEBP4 on Lipopolysaccharide (LPS)/ D galactosamine (D-GalN)-induced ALI. PEBP4 was downregulated after treatment with LPS/D-GalN in wild-type mice. PEBP4-knockout aggravated liver damage and repressed liver functions, including hepatocellular edema, red blood cell infiltration, and increased Aspartate aminotransferase (AST)/Alanine aminotrans-ferase (ALT) activities. The inflammatory response was promoted through increased neutrophil infiltration, Myeloperoxidase (MPO) activities, and cytokine secretions (interleukin-1β, IL-1β; tumor necrosis factor alpha, TNF-α; and cyclooxygenase-2, COX-2) in PEBP4-knockout mice. PEBP4-knockout also induced an apoptotic effect, including increasing the degree of apoptotic hepatocytes, the expressions, and activities of caspases, and pro-apoptotic factor Bax while decreasing anti-apoptotic factor Bcl-2. Furthermore, the data demonstrated the levels of Toll-like receptor 4 (TLR4), phosphorylation-inhibitor of nuclear factor kappaB Alpha(p-IκB-α), and nuclear factor kappaB(NF-κB) p65 were upregulated, while the expressions of cytoplasmic IκB-α and NF-κB p65 were downregulated after PEBP4-knockout. More importantly, both the NF-κB inhibitor (Ammonium pyrrolidinedithiocarbamate, PDTC) and a small-molecule inhibitor of TLR4 (TAK-242) could inhibit TLR4/NF-κB signaling activation and reverse the effects of PEBP4-knockout. In summary, the data suggested that PEBP4 protects against LPS/D-GalN–induced ALI, and the effect is partly mediated by inhibition of the TLR4/NF-κB signaling pathway.